1995
DOI: 10.1142/9789812795892_0035
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chemistry and Magnetic Properties of Layered Metal Oxides Possessing the K2NiF4 or Related Structures

Abstract: There is increasing interest in recent years in the structural chemistry and properties of layered metal oxides possessing the K2NiF4 or related structures. Many new oxides of this structure exhibiting novel properties are being reported from time to time in the literature. The crystal chemistry of the oxides of the general formula A2B04 with particular reference to the stability of the K2NiF4 structure and the relations between the different structures exhibited by this family of oxides is discussed. Non-stoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The abnormally reduced Qf value is observed in the range of 0.05 < x < 0.4, and the most deteriorated Qf value of 70 500 GHz is located at x = 0.2. The reasons for the variation of Qf value of Sr 1+ x La 1− x Al 1− x Ti x O 4 solid solution can be interpreted by several factors as follows: Considering the K 2 NiF 4 structure of Sr 1+ x La 1− x Al 1− x Ti x O 4 solid solution, the size adaptability between perovskite layer and rocksalt layer is usually reflected by the tolerance factor t 21−24. t=[(1+x)rnormalSnormalr2++(1x)rnormalLnormala3+]/2+rO22[(1x)rnormalAnormall3++xrnormalTnormali4++rnormalO2] where rSr2+, rLa3+, rAl3+, rTi4+, and rO2 are the effective radii of Sr 2+ , La 3+ , Al 3+ , Ti 4+ , and O 2− , respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The abnormally reduced Qf value is observed in the range of 0.05 < x < 0.4, and the most deteriorated Qf value of 70 500 GHz is located at x = 0.2. The reasons for the variation of Qf value of Sr 1+ x La 1− x Al 1− x Ti x O 4 solid solution can be interpreted by several factors as follows: Considering the K 2 NiF 4 structure of Sr 1+ x La 1− x Al 1− x Ti x O 4 solid solution, the size adaptability between perovskite layer and rocksalt layer is usually reflected by the tolerance factor t 21−24. t=[(1+x)rnormalSnormalr2++(1x)rnormalLnormala3+]/2+rO22[(1x)rnormalAnormall3++xrnormalTnormali4++rnormalO2] where rSr2+, rLa3+, rAl3+, rTi4+, and rO2 are the effective radii of Sr 2+ , La 3+ , Al 3+ , Ti 4+ , and O 2− , respectively .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] This structure possesses ABO 3 (B = transition metal ion), perovskite-type, layers between rock-salt A-O layers, B-O-B interactions occurring only in the ab plane have been investigated. 4 The K 2 NiF 4 -type structure; Sr 2 RuO 4 has also been investigated as a spin-triplet unconventional superconductor with T c ∼ −271.66 • C. 5 Recently, it has been reported that the Sr 2 Ru 1−x Ti x O 4 solid solution, with the substitution of non-magnetic Ti 4+ (3d 0 ) for Ru 4+ (4d 4 ) in Sr 2 RuO 4 , changes from spin-triplet superconductivity to magnetic ordering for x ≥ 0.25. 6,7 Polycrystalline samples of Sr 2 Ru 1−x Ti x O 4 with composition 0 ≤ x ≤ 1, on the other hand, have been synthesized and the electrical resistivities determined at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation of the MnO 6 octahedra is governed by the tolerance factor (t) [44,45], which is defined as With a view to understand the electrical and magnetic properties with the variation of A-site ionic radii, the average A-site ionic radii 〉 〈 A r and size variance factor ( 2 σ ) have been calculated from the standard ionic radii [46] of nine-fold coordination and are given in Table 2. The variation 2 σ with 〉 〈 A r is shown in Fig.2.…”
Section: Resultsmentioning
confidence: 99%